2019
DOI: 10.21276/ijcmr.2019.6.9.5
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Etiological Profile of Non-Compressive Myelopathies in a Tertiary Care Hospital in Central Tamilnadu

Abstract: Introduction: Non compressive myelopathy is defined as "spinal cord dysfunction in the absence of clinico-radiological evidence of spinal cord compression." It can result from demyelinating, infectious, autoimmune, vascular, degenerative and metabolic disorders in the absence of demonstrable compression by imaging techniques. We aimed in analyzing the etiological profile of non-compressive myelopathies in a tertiary care hospital of Central Tamil nadu. Material and Methods: In the Neurology department, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
6
Order By: Relevance
“…In a study conducted by Thangaraj et al, 61.33 percent of the patients were males while the remaining were females. 5,6…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Thangaraj et al, 61.33 percent of the patients were males while the remaining were females. 5,6…”
Section: Gendermentioning
confidence: 99%
“…Thangaraj et al in their study, reported that 32 percent and 22.67 percent of the patients belonged to the age group of 40 to 50 years and 20 to 30 years respectively [5][6][7]. …”
mentioning
confidence: 99%
“…2 Terminologi mielopati kompresif dan nonkompresif diperkenalkan oleh Siccard dan Frostier pada tahun 1921 berdasarkan pemeriksaan mielografi. 1,3 Mielopati nonkompresif didefinisikan sebagai disfungsi medula spinalis tanpa adanya bukti klinis dan radiologis kompresi medula spinalis. 3 Lesi kompresi disingkirkan dengan magnetic resonance imaging (MRI).…”
unclassified
“…1,3 Mielopati nonkompresif didefinisikan sebagai disfungsi medula spinalis tanpa adanya bukti klinis dan radiologis kompresi medula spinalis. 3 Lesi kompresi disingkirkan dengan magnetic resonance imaging (MRI). [2][3][4] Penatalaksanaan mielopati sebagian besar adalah medikamentosa, sebagian kasus mielopati kompresif yang merupakan kondisi gawat darurat dengan penatalaksanaan bedah.…”
unclassified
See 1 more Smart Citation